Cnn dynamics drive centrosome size asymmetry to ensure daughter centriole retention in Drosophila neuroblasts. - Conduit, P; Raff, J (2010)
Centrosomes comprise a pair of centrioles surrounded by an amorphous network of pericentriolar material (PCM). In certain stem cells, the two centrosomes differ in size, and this appears to be important for asymmetric cell division [1, 2]. In some cases, centrosome asymmetry is linked to centriole age because the older, mother centriole always organizes more PCM than the daughter centriole, thus ensuring that the mother centriole is always retained in the stem cell after cell division [3]. This has raised the possibility that an "immortal" mother centriole may help maintain stem cell fate [4, 5]. It is unclear, however, how centrosome size asymmetry is generated in stem cells. Here we provide compelling evidence that centrosome size asymmetry in Drosophila neuroblasts is generated by the differential regulation of Cnn incorporation into the PCM at mother and daughter centrioles. Shortly after centriole separation, mother and daughter centrioles organize similar amounts of PCM, but Cnn incorporation is then rapidly downregulated at the mother centriole, while it is maintained at the daughter centriole. This ensures that the daughter centriole maintains its PCM and so its position at the apical cortex. Thus, the daughter centriole, rather than an "immortal" mother centriole, is ultimately retained in these stem cells.